Patient satisfaction and cost analysis of analgesia management for post-operative procedures in HTAA : PCA vs. conventional method - Ramli, Siti Norsyuhada; Mazlan, Muhammad Alif; Mat Yusof, Afzan; Md Isa, Muhammad Lokman (Malaysian Public Health Physicians Association, 2019)
Acute pain service (APS) offer several techniques to the post-operative patient in controlling and relieving the pain such as intravenous infusion, patient-controlled analgesia, epidural infusion, subcutaneous or intramuscular injection and intrathecal administration. The effectiveness of and satisfaction towards APS is not clearly defined. Therefore, the aim of this study is to conduct the cost analysis and comparison between these techniques and patient satisfaction. The study design for cost analysis was retrospective study. The means of the data were calculated based on Integration Store of Hospital Tengku Ampuan Afzan records. In addition, the evaluation of patient’s satisfaction was conducted by using a crosssectional study design. The mean of the data was calculated and analysed by using Chi-square test. The total cost required to prepare PCA for post-operative patient was the highest with RM 8810.98. Meanwhile, the cost for subcutaneous morphine injection, epidural infusion and peripheral block injection were RM 2.11, RM 5323.95 and RM 4.95 respectively. However, when taking into the aspect of patient’s satisfaction, PCA has the highest level of excellent performance with 54.6% compare to EDA (33%) and BLOCK (12.4%) with the p-value is less than 0.05. In conclusion, every drug has its own side effects. As the healthcare provider, it is a need to ensure drugs that were given to the patients are at the very minimum risk of having the side effects. Based on the findings of this study, it could be said that both drugs have lower percentage of people experienced the side effect after treated with the drugs. Therefore, the future study should be more focusing on the side effect of the drugs used. In terms of cost spent for the methods, the PCA regimen is more likely expensive compared to the conventional methods. However, based on survey among the patients, PCA-treated patients expressed higher satisfaction compared to the conventional regimen of pain management.